Effect of Sweet Potato Starch on Rheological Properties and Emulsion Stability of Salad Dressings - Cynthia Torres-Álvarez; Karla G. García-Alanís; Carlos A. Amaya-Guerra; Ethel D. Cabello-Ruiz; Abelardo Chávez-Montes; Sandra L. Castillo-Hernández; Minerva Bautista-Villarreal (Polysaccharides, 2025)
Due to its gelling and thickening properties, sweet potato starch (Ipomoea batatas L.) could be a promising ingredient to improve characteristics such as the viscosity and consistency of foods like dressings. The objective of this study was to use sweet potato starch by adding it to salad dressing-type emulsion formulations. Sweet potato starch was characterized (microscopic appearance, granule size, and thermal properties). Four formulations (F1–F4) were developed incorporating different amounts of sweet potato starch (2 and 4%), and were characterized by particle size, emulsion stability, rheology, and sensory analysis. The starch granules were oval shaped, with a size range of 10–33 μm, and a temperature and enthalpy gelatinization (ΔH) of 69.08 °C and 10.72 J/g, respectively. The formulations were evaluated for 30 days, the particle size had a range of 2.18–13.88 μm, the emulsion stability was 98.89–100%, all formulations presented a creaming index at 0%, and the coalescence rate obtained values between −2.33 × 10−8 and 7 × 10−8Kc (s−1) showing a significant difference. The consistency coefficient (K) was obtained, 2.477–35.207 Pa·sn, and there was no significant difference between F1 and F2 with respect to a commercial dressing. In the sensory analysis, F2 presented greater acceptance. The values obtained suggest that sweet potato starch could be used in this type of food, showing similarities to the commercial brand.